Monitoring physical match performance relative to peak locomotor demands: implications for training professional soccer players - Oliva-Lozano, J. M.; Riboli, A.; Fortes, V.; Muyor, J. M. (Biology of Sport, 2023)
This study aimed to analyse physical performance relative to peak locomotor demands of match play. Data were collected during 13 professional soccer matches. Initially, the 1-minute peak values were registered in each match, including the percentage of the total distance (TD), high-speed running distance (HSRD), sprinting distance (SPD), and high-metabolic load distance (HMLD), and a total of high-intensity accelerations and decelerations (Acc+Dec). Secondly, the time (measured in minutes) spent at different percentage ranges for the 1-minute peak values registered in each match was calculated. Thirdly, the physical performance required in the different percentage ranges for the 1-minute peak values were obtained. Finally, the time and physical performance required above the 90-minute average demands were calculated. The 90-minute average for all playing positions represented ~53% of the total distance (TD), ~23.4% of high-metabolic load distance (HMLD), ~16% of high-speed running distance (HSRD), ~11% of the total of high-intensity accelerations and decelerations (Acc+Dec), and ~6% of sprinting distance (SPD) for the 1-minute peak values. Likewise, statistically significant differences ( p < 0.05) in the physical performance and time spent between specific percentage ranges for the 1-minute peak locomotor demands were also noted. In addition, all the variables reported that the physical performance required for above 90-minute average demands were significantly greater (p < 0.05) than the 90-minute average demands. Therefore, these findings may guide the prescription of training intensity by considering the physical performance relative to the peak locomotor demands of match play.